Mindfulness on Stress Reduction and Concentration Improvement of Accounting Students: Mindfulness terhadap Penurunan Stres dan Peningkatan Konsentrasi Mahasiswa Akuntansi - Riefaldy, Muhammad; Khamal , Khamal; Komara , Acep; Senja, Nurul (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic stress is common among university students and can impair concentration. Specific Background: Mindfulness is known to reduce stress but its specific component—acceptance without judgment—has been underexplored in academic contexts. Knowledge Gap: Few studies isolate this component's effect on stress and concentration. Aim: This study examines the impact of mindfulness on stress reduction and concentration improvement among students. Results: Based on a correlational study with 82 students, mindfulness significantly reduced stress (t = 3.913; p < 0.001) but had no significant effect on concentration (t = 0.935; p = 0.353). Novelty: The study isolates the role of acceptance without judgment in academic mindfulness. Implications: Mindfulness is effective for stress management but insufficient alone to enhance concentration, requiring integrated academic strategies.Highlight : Mindfulness is effective in reducing students' academic stress levels. It does not significantly improve students' concentration. A more comprehensive approach is needed to enhance academic focus. Keywords : Mindfulness, Academic Stress, Concentration, University Students, Economics Education